A strategic impact assessment of hydropower plants in alpine and non-alpine areas of Europe. (15th September 2019) - Mahmud, M. A. Parvez; Huda, Nazmul; Farjana, Shahjadi Hisan; Lang, Candace
Highlights: Environmental impacts of hydropower plants in Europe is investigated by LCA analysis. Impacts are estimated by the ReCiPe 2016, Impact 2002+, and Eco-points 97 methods. Hydropower plants of alpine regions are found least hazardous to the environment. Plants of non-alpine areas are 10 times responsible for climate change than alpines. Abstract: Hydropower is the widely used source of clean energy which includes some hazardous emissions that affect human health, ecosystems, and resources. However, in spite of an enormous amount of hydropower generation in Europe, no research has been carried out in evaluating the hazardous emissions from the plants located in alpine and non-alpine areas. Therefore, this paper will analyse the comparative environmental impacts of hydropower plants in alpine and non-alpine areas of Europe by a systematic life-cycle assessment (LCA) approach. The impacts are estimated by the ReCiPe 2016, Impact 2002+, Eco-points 97 methods under a number of effect-assessing indicators such as global warming, ozone formation, eco-toxicity, water consumption, acidification, eutrophication, ionizing radiation, carcinogenic radiation, ozone depletion, and land use. Moreover, the fossil-fuel-based power consumptions and the greenhouse-gas emissions in the life-cycle of hydropower plants in both locations are estimated using the Cumulative Energy Demand (CED) and the Intergovernmental Panel on Climate Change (IPCC) methods, respectively. The outcomes reveal that hydropower plants of alpine regions offer a better environmental profile for the global-warming indicator ( 2.97 × 10 - 5 kg CO2 -eq/MJ) than non-alpine plants ( 3.92 × 10 - 4 kg CO2 -eq/MJ), but the effects are nearly identical for the other indicators. Overall, the hydropower plants of non-alpine regions are responsible for climate change with a rate 10 times as high as for alpine ones. The findings of this research will play a pivotal role in promoting sustainable production of hydropower, especially the full potentials of the alpine region, and thus leading towards environmentally friendly clean renewable electricity generation.